Mandatory requirements for pediatric drug development in the EU and the US for novel drugs—A comparative study - Christiansen, Helle; De Bruin, Marie L.; Hallgreen, Christine E. (Frontiers in Medicine, 2022)
Mandatory pediatric legislation has been implemented in the European Union (EU) and the United States (US) to increase research and the availability of drugs for the pediatric population. Differences in the legislative framework can cause different pediatric requirements for similar indications granted for similar drugs across jurisdictions. This cross-sectional study compares the pediatric requirements for therapeutic indications granted at the time of initial approval for novel drugs approved in the two regions from 2010 to 2018. We collected the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) decisions to grant a waiver and/or to agree on a pediatric development plan and deferrals hereof at marketing authorization (MA) from publicly available documents. An agreed pediatric development plan was required for 66% (n=188/285) and 63% (n=134/212) of the indications granted in the EU and the US at the time of approval, respectively. Almost all (EU; 98%, US; 89%) were deferred until after MA. Based on the broad scope of the EU Paediatric Regulation, an additional 36 PIPs originated from the indications granted at MA. In the subset of indications granted for drugs approved in both the EU and the US (n=232), significantly more indications resulted in an agreed pediatric development plan for one or more subsets of the pediatric population in the EU (n=185) as compared to the US (n=82). This was based on the exemption of orphan designated drugs in the US and the broader scope of the EU Paediatric Regulation. However, indications subject to the mandatory pediatric legislation in both regions (n=131) most often had similar regulatory requirements for the inclusion of the pediatric population from the EMA and the US FDA (83%, n=109). In conclusion, when comparing mandatory pediatric requirements, more pediatric development plans were agreed upon in the EU than in the US, in line with the broader mandates of the EU Paediatric Regulation. However, authorities most often had similar regulatory requirements when an indication was subject to pediatric legislation in both regions.